Potassium 4-Iodylbenzenesulfonate (PIBS): An Efficient Recyclable Hypervalent Iodine Reagent for Iodo-functionalization of Alkenes, Alkynes and Ketones; Current Organic Synthesis; Vol. 13, iss. 6 - Mironova I. A. Irina Andreevna; Yusubova R. Ya. Roza Yavidovna; Kukurina O. S. Olga Sergeevna; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Zhdankin V. V. Viktor Vladimirovich (2016, 2016)
Title screen